Virtual reality training for intraoperative imaging in orthopaedic surgery: an overview of current progress and future direction - Pratap, Jayanth; Laane, Charlotte; Chen, Neal; Bhashyam, Abhiram (Frontiers in Virtual Reality, 2024)
Trauma and orthopedic surgery commonly rely on intraoperative radiography or fluoroscopy, which are essential for visualizing patient anatomy and safely completing surgical procedures. However, these imaging methods generate ionizing radiation, which in high doses carries a potential health risk to patients and operating personnel. There is an established need for formal training in obtaining precise intraoperative imaging while minimizing radiation exposure. Virtual reality (VR) simulation serves as a promising tool for orthopaedic trainees to develop skills in safe intraoperative imaging, without posing harm to patients, operating room staff, or themselves. This paper aims to provide a brief overview of literature surrounding VR training for intraoperative imaging in orthopaedic surgery. In addition, we discuss areas for improvement and future directions for development in the field.